TOEFL iBT premier 2016-2017. - Kaplan Test Prep (Firm); Kaplan Publishing (New York : Kaplan Publishing, 2015)
"The TOEFL iBT tests your abilities in Reading, Writing, Listening, and Speaking. Kaplan's TOEFL iBT Premier with Practice Tests presents the most important language skills and strategies you need to succeed on this test. The TOEFL is required worldwide for international students who want to study abroad. Kaplan's comprehensive guide gives you exactly what you will need to get ready for Test Day."--Amazon.com.
English Language & Literature.
Keywords: Test of English as a Foreign Language -- Study guides -- Periodicals; English language -- Examinations -- Study guides -- Periodicals; English language -- Textbooks for foreign speakers -- Periodicals; English language; English language -- Examinations; Test of English as a Foreign Language; Periodicals; Study guides; Textbooks; Textbooks -- for foreign speakers; Study guides; Textbooks; Periodicals